Safety and efficacy of l‐leucine produced by fermentation with Escherichia coli NITE BP‐02351 for all animal species. (3rd May 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐leucine produced by fermentation with Escherichia coli NITE BP‐02351 when used as nutritional additive or as feed flavouring compound in feed and water for drinking for all animal species. The product under assessment is l ‐leucine produced by fermentation with a genetically modified strain of E. coli (NITE BP‐02351). The production strain and its recombinant DNA were not detected in the final products. l ‐Leucine, manufactured by fermentation with E. coli NITE BP‐02351, does not give rise to any safety concern to the production strain. The use of l ‐leucine produced with E. coli NITE BP‐02351 is safe for the target species when used to supplement the diet in appropriate amounts. It is safe at the proposed use level of 25 mg/kg when used as flavouring compound for all animal species. The use of l ‐leucine produced by fermentation with E. coli NITE BP‐02351 in animal nutrition raises no safety concerns for consumers of animal products. The additive is not irritating to the skin or eyes and is not a skin sensitiser. There is a risk for persons handling the additive from the exposure to endotoxins by inhalation. The use of l ‐leucine produced by  E. coli NITE BP‐02351 as feed additive does not represent a risk to the environment. The additive l ‐leucine produced by E. coli NITE BP‐02351 is regarded as an effective source of the amino acid l ‐leucine when used as nutritional additive. For the supplemental l ‐leucine to be as efficacious in ruminants as in non‐ruminant species, it requires protection against degradation in the rumen. It is also considered efficacious as feed flavouring compound under the proposed conditions of use.